1996
DOI: 10.1111/j.1467-9280.1996.tb00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the Self-Concept a Habitual Referent in Judgments of Similarity?

Abstract: People typically provide higher similarity ratings in response to the question "HoII' similar is the typical preppie to you?" than to the question "HoII' similar are you to the typical preppie?" Observed asymmetries in comparisons of the self and person prototypes hm'e been offered as el'idence that the self-concept acts as a habitual reference point in social judgmelll. HOII'ever, such a task does not test the habitual placemelll of a concept ill the referell1 position of a comparisoll. In this sllldy, partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 21 publications
2
47
2
Order By: Relevance
“…Predictions about the self varied more than predictions about another person. This is consistent with the suggestion of a more elaborate self-knowledge than other-knowledge (Catrambone et al, 1996;Sande et al, 1988). Unexpectedly, however, this effect was only present for a similar other.…”
Section: Discussionsupporting
confidence: 80%
“…Predictions about the self varied more than predictions about another person. This is consistent with the suggestion of a more elaborate self-knowledge than other-knowledge (Catrambone et al, 1996;Sande et al, 1988). Unexpectedly, however, this effect was only present for a similar other.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, due to the randomized design, such a preference should have applied equally to all stimulus pairs, and could hardly have changed the weighting. Catrambone, Beike, and Niedenthal (1996) found, consistent with Tversky's (1977) feature-matching theory, higher similarity judgments of pairs of countries (i.e., "How similar is A to B?") when B (the referent) was highly familiar and A (the subject) less familiar than were found in the reverse case.…”
Section: Resultssupporting
confidence: 65%
“…In support of this position, Tversky (1977 ;Tversky & Gati, 1978) found that the preferred direction of similarity comparison was commonly the one with the greater degree of judged similarity . Such asymmetries in similarity judgments have been obtained in areas as diverse as music perception (Bartlett & Dowling, 1988) and self-other similarity judgments (Catrambone, Beike, & Niedenthal, 1996 ;Holyoak & Gordon, 1983 ;Srull & Gaelick, 1983) .…”
Section: Previous Accounts Of Comparison Asymmetries Feature Contrastmentioning
confidence: 91%
“…One consistent finding in the literature is that subjects rate others (both individuals and groups) and being more similar to the self than vice versa (e .g., Catrambone, Beike, & Niedenthal, 1996 ;Holyoak & Gordon, 1983 ;Srull & Gaelick, 1983) . A second finding is that subjects are generally more willing to make inferences and predictions from the self to others than vice versa (e.g., Kunda & Nisbett, 1988 ;McFarland & Miller, 1990) .…”
Section: Systematicity and Related Notionsmentioning
confidence: 99%